The Use of Debate Method to Improve Students’ Speaking Skill - Werdiningsih, Indah (Jetlal, 2018)
Speaking is a crucial part of the language learning process. However, many students find speaking as one of the most difficult skills in English. Therefore, the researcher wants to improve the students’ speaking ability through the suitable teaching method, in this case the debate. The objective of this research referring to the research problem is to find out how the debate method can improve speaking ability. Based on the research problem and the relevant theory, the hypothesis of this research is described as follows: Debate method improves the speaking ability of the fifth semester students of Universitas Muhammadiyah Jember in the 2017 / 2018 academic year by developing their activeness in expressing oral argument logically in a systematic way. The design of this research is classroom action research. The research subject is the fifth semester class consisting of 34 students. Test and observation are used to obtain the data. The data collection involved a number of instruments namely Test of Speaking English and Speaking Rubric. It was then evaluated by using speaking rubric covering fluency, pronunciation, vocabulary and grammar. Debate method improves the students’ speaking ability in two cycles from M = 61.84 in Cycle 1 to M = 70.34 in Cycle 2 and the percentage of students scored (E = 66.67%) in Cycle 1 to (E = 83.34%) in Cycle 2. The observation result from 56.15% students’ activeness in Cycle 1 to 85.29% students’ activeness in Cycle 2. Based on the data above, there was significant impact of Cycle 2 implementation on the students’ speaking ability. It can be concluded that debate method is able to improve the students’ speaking ability.